2017
DOI: 10.1182/bloodadvances.2017005447
|View full text |Cite
|
Sign up to set email alerts
|

Immune signatures associated with improved progression-free and overall survival for myeloma patients treated with AHSCT

Abstract: Key Points Specific immune phenotypes were predictive of long-term survival for MM patients undergoing transplantation. MRD status and use of maintenance therapy were associated with unique immune profiles predictive of outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
44
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 30 publications
1
44
1
Order By: Relevance
“…1,3 Early studies observed that long-term disease-free survival (DFS) of leukemia patients who received ab T-cell-depleted (TCD) partially mismatched related donor (PMRD) transplants had high numbers of circulating gd T cells after HSCT. 4,5 More recent studies with non-TCD PMRD 6 and autologous HSCT 7 further corroborated these findings, describing an improved survival in patients with higher gd T-cell counts posttransplantation. These studies suggested that the recovery of gd T cells after HSCT is critical for an efficient GVL effect 3 and possibly to control infections, 8 helping to pave the way to a more broad application of graft manipulation strategies.…”
Section: Introductionmentioning
confidence: 72%
See 4 more Smart Citations
“…1,3 Early studies observed that long-term disease-free survival (DFS) of leukemia patients who received ab T-cell-depleted (TCD) partially mismatched related donor (PMRD) transplants had high numbers of circulating gd T cells after HSCT. 4,5 More recent studies with non-TCD PMRD 6 and autologous HSCT 7 further corroborated these findings, describing an improved survival in patients with higher gd T-cell counts posttransplantation. These studies suggested that the recovery of gd T cells after HSCT is critical for an efficient GVL effect 3 and possibly to control infections, 8 helping to pave the way to a more broad application of graft manipulation strategies.…”
Section: Introductionmentioning
confidence: 72%
“…Eleven studies were used in meta-analysis, enrolling 919 patients. [4][5][6][7][8]17,[53][54][55][56][57] From those reports, 8 evaluated gd T-cell reconstitution after HSCT and 3 evaluated gd T-cell content in the graft ( Table 2).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations